2023
DOI: 10.3389/fmicb.2023.1142536
|View full text |Cite
|
Sign up to set email alerts
|

Industrial applications of fungal lipases: a review

Abstract: Fungal lipases (triacylglycerol acyl hydrolases EC 3.1.1.3) are significant industrial enzymes and have several applications in a number of industries and fields. Fungal lipases are found in several species of fungi and yeast. These enzymes are carboxylic acid esterases, categorized under the serine hydrolase family, and do not require any cofactor during the catalyzing of the reactions. It was also noticed that processes including the extraction and purification of lipases from fungi are comparatively easier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 167 publications
0
14
0
Order By: Relevance
“…Our experimentation above used an ideal system for the biotic degradation of PLLA as proteinase K is the leading enzyme for the catalysis of PLLA enzymatic hydrolysis. , To determine if the trends demonstrated are more generalizable, the biodegradability experiments were repeated utilizing another esterase, triacylglycerol lipase. Lipases are present in a high majority of living organisms, with a large number of fungi also producing lipases . Tokiwa et al, demonstrated the ability of lipase to degrade synthetic polyesters, and Alejandra et al, confirmed lipase’s degradation capabilities in poly­(3-hydroxybutyrate- co -4-hydroxybutyrate). , Ultimately, lipase is a readily available enzyme and shown to degrade polyesters. , Figure shows that lipase induces a trend in enzymatic hydrolysis near identical to that of proteinase K. The presence of the identical catalytic triad in both lipase and proteinase K may be the cause for the similar response, with both proteinase K and lipase exhibit the ‘catalytic triad of aspartic acid (Asp), histidine (His), and serine (Ser) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our experimentation above used an ideal system for the biotic degradation of PLLA as proteinase K is the leading enzyme for the catalysis of PLLA enzymatic hydrolysis. , To determine if the trends demonstrated are more generalizable, the biodegradability experiments were repeated utilizing another esterase, triacylglycerol lipase. Lipases are present in a high majority of living organisms, with a large number of fungi also producing lipases . Tokiwa et al, demonstrated the ability of lipase to degrade synthetic polyesters, and Alejandra et al, confirmed lipase’s degradation capabilities in poly­(3-hydroxybutyrate- co -4-hydroxybutyrate). , Ultimately, lipase is a readily available enzyme and shown to degrade polyesters. , Figure shows that lipase induces a trend in enzymatic hydrolysis near identical to that of proteinase K. The presence of the identical catalytic triad in both lipase and proteinase K may be the cause for the similar response, with both proteinase K and lipase exhibit the ‘catalytic triad of aspartic acid (Asp), histidine (His), and serine (Ser) .…”
Section: Resultsmentioning
confidence: 97%
“…Lipases are present in a high majority of living organisms, with a large number of fungi also producing lipases. 34 Tokiwa et al, demonstrated the ability of lipase to degrade synthetic polyesters, and Alejandra et al, confirmed lipase's degradation capabilities in poly(3-hydroxybutyrate-co-4-hydroxybutyrate). 35,36 Ultimately, lipase is a readily available enzyme and shown to degrade polyesters.…”
Section: Trends Utilizing Other Enzymesmentioning
confidence: 97%
“…Lipases are considered a group of potential industrial enzymes that can catalyze the hydrolysis of triglycerides [soluble fats], liberating monoglycerides. Diglycerides, glycerol and free fatty acids across the oil-water interface [69]. Lipases are valuable enzymes as they accept a wide range of substrates, they are stable and active in organic solvents, and are available from several microbes.…”
Section: Cynodon Dactylonmentioning
confidence: 99%
“…Lipases have several biotechnologically interesting characteristics. The extracellular lipolytic activity of Bacillus subtilis was first observed in 1979 by Kennedy and Lennarz . However, intensive molecular research did not start over a decade later in 1992, with the cloning and sequencing of a lipase gene, lipA (lipaseA), followed by recombinant expression, purification, and functional and structural characterizations …”
Section: Introductionmentioning
confidence: 99%